Adolescent Attachment Profiles Are Associated With Mental Health and Risk-Taking Behavior - Flykt, Marjo; Vänskä, Mervi; Punamäki, Raija-Leena; Heikkilä, Lotta; Tiitinen, Aila; Poikkeus, Piia; Lindblom, Jallu (Frontiers in Psychology, 2021)
This person-oriented study aimed to identify adolescents’ hierarchical attachment profiles with parents and peers, and to analyze associations between the profiles and adolescent psychosocial adjustment. Participants were 449 Finnish 17–19-year-olds reporting their attachments to mother, father, best friend, and romantic partner and details on mental health (internalizing symptoms, inattention/hyperactivity, and anger control problems) and risk-taking behavior (substance use and sexual risk-taking). Attachment was measured with Experiences in Close Relationships - Relationship Structures (ECR-RS); internalizing, inattention/hyperactivity, and anger control problems with Self-Report of Personality ─ Adolescent (SRP─A) of the Behavior Assessment System for Children, third edition (BASC-3); substance use with the Consumption scale of the Alcohol Use Disorders Identification Test (AUDIT-C) and items from the Finnish School Health Promotion Study; and sexual risk-taking behavior with the Cognitive Appraisal of Risky Events (CARE). Latent profile analysis identified five attachment profiles: “All secure” (39%), “All insecure” (11%), “Parents insecure – Peers secure” (21%), “Parents secure – Friend insecure” (10%), and “Parents secure – Partner insecure” (19%). “All insecure” adolescents showed the highest and “All secure” adolescents the lowest levels of mental health problems and substance use. Further, parental attachment security seemed to specifically prevent substance use and anger control problems, while peer attachment security prevented internalizing problems. Our findings help both understand the organization of attachment hierarchies in adolescence and refine the role of specific attachment relationships in psychosocial adjustment, which can be important for clinical interventions in adolescence.